Fenomena Consumer Lock-In dalam Pasar Amdk dilihat dari Aspek Hukum Persaingan Usaha di Indonesia - Daniel Chesar Prasetya Dirgantara (UNES Law Review, 2023)
Monopolistic practices are prohibited in business competition because their impact can create imbalances in the market or in other words can create unfair business competition. In this research, the author brings up the topic of the existence of Consumer Lock-In practices. Business competition in the Bottled Drinking Water market or commonly known as AMDK. In practice, the sale of bottled drinking water uses the gallon exchange method which, if examined further, can result in consumer dependence which has implications for the difficulty of other business actors to enter the same market. On the other hand, the commonality of the practice makes its position unclear whether it is classified as prohibited under Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. This research uses doctrinal research methods using secondary data consisting of laws and regulations, books, scientific magazines, clippings, journals, papers, internet sites and other data sources. In closing, the author intends to convey that the practices carried out by business actors in the bottled water market have the potential to harm fair business competition.